Extracting and analyzing micronuclei from mouse two-cell embryos fertilized with freeze-dried spermatozoa - Ikue Shibasaki; Hinata Sugiyama; Yuko Kamada; Hiroaki Nagatomo; Daiyu Ito; Sayaka Wakayama; Masatoshi Ooga; Tsuyoshi Kasai; Takashi Kohda; Teruhiko Wakayama (Communications Biology)
Abstract Abnormal chromosome segregation (ACS) in preimplantation embryos causes miscarriages. For a normal pregnancy, it is necessary to reduce ACS occurrences in embryos. However, the causes of such abnormalities are unclear because no method to extract the segregated chromosomes from the blastomeres for detailed analysis. This study attempted to extract micronuclei derived from segregated chromosomes of mouse embryos. Some micronuclei in blastomeres were bound to the nucleus by DNA cross-links, some were bound to tubulin, and about half of the micronuclei had major satellite regions. By depolymerizing the cytoskeleton of blastomeres with cytochalasin B and colcemid, some micronuclei could be extracted from blastomeres of ACS embryos using a glass needle of a micromanipulator. DNA-sequencing results of each extracted micronucleus revealed that chromosomes in micronuclei were randomly selected, usually only one, and often contained a portion rather than the full length of the chromosome. This study allows a detailed analysis of micronuclei and facilitates the mechanism of the causes of ACS in embryos.